The Relationship between Pulse Wave Velocity and Coronary Artery Stenosis and Percutaneous Coronary Intervention: a retrospective observational study. Issue 1 (December 2017) - Joo, Hyung; Cho, Sang-A; Cho, Jae-Young; Park, Jae; Hong, Soon; Yu, Cheol; Lim, Do-Sun
Abstract Background Arterial stiffness has been suggested as a valuable predictor of coronary artery stenosis (CAS). However, little data are available on aortic stiffness and CAS in patients who have previously undergone percutaneous coronary artery intervention (PCI). The aim of this study was to investigate the association of arterial stiffness to CAS in patients with a history of PCI and those without a history of PCI. Methods We retrospectively studied 1093 consecutive patients who had undergone coronary angiography (CAG). Arterial stiffness was determined by brachial-ankle pulse wave velocity (baPWV) measured prior to CAG. Results In patients without a history of PCI, baPWV significantly increased in patients with CAS compared to that in patients without CAS (p  < 0.001). However, among patients with a history of PCI, there was no significant difference in baPWV. Multivariate logistic regression analysis demonstrated that baPWV was an independent risk predictor for CAS in patients without a history of PCI, but not in those with a history of PCI (OR 1.106, 95% CI 1.039–1.177, p  = 0.002). In CAS patients without a history of PCI, increased baPWV was significantly associated with multiple cardiovascular risk factors, multivessel involvement, and anatomical severity. Conclusions Prediction of CAS by baPWV is significantly attenuated in patients with a history of PCI.